Climate change impact on water availability in the olifants catchment (South Africa) with potential adaptation strategies. (December 2020) - Olabanji, Mary Funke; Ndarana, Thando; Davis, Nerhene; Archer, Emma
Abstract: Increasing population and economic growth has intensified water supply pressure on the Olifants River Basin causing it to become water-stressed. Climate change is expected to aggravate existing water supply challenges in the basin if urgent interventions are not implemented. This study evaluates the impacts of climate change on water availability and demand in the Olifants River Basin of South Africa, and assesses to what extent a combination of management strategies can mitigate current and longer term impacts using the Water Evaluation and Planning (WEAP) model. The results demonstrated by the two projected climate change scenarios (RCP4.5 and RCP8.5) showed a rise in temperature of approximately 1 °C–4 °C, and a decrease in precipitation of 5%–30%, as compared to the baseline climate of 1976–2005. Results also showed that pressure on water supply due to increased economic activities and a decline in streamflow will increase unmet water demand by 58% and 80% for the mid and end century periods respectively. Results further revealed that the combination of management measures proposed by decision makers is expected to decrease future unmet water demand from 1006MCM to 398MCM, 1205MCM to 872MCM and 1251MCM to 940MCM for reference, RCP4.5 and RCP 8.5 scenario respectively. The study therefore concludes that the combination of management strategies provides a much better and more efficient solution to water scarcity issues in the basin, compared to a reliance on a single strategy. Graphical abstract: Image 1 Highlights: Changes in temperature and precipitation is expected in the Olifants catchment. WEAP hydrological model successfully simulated water availability and demand. Streamflow is expected to reduce in the catchment. Water demand is anticipated to increase in the future. Combination of management strategies will reduce the short-term impact of climate change.